The impact of mobile service quality on satisfaction and loyalty: a study of online food delivery in Thailand - Sribusdee, Nannapas (2022)
The development of technology and the internet have changed customers' eating habits. The online food delivery (OFD) sector is expanding, aided by the pandemic. As a result, business is becoming more competitive. In Thailand, various players invest heavily to stay on top of the market. However, none of them can turn it as profit. This study aimed to broaden understanding of mobile service quality by investigating customer perceived mobile service quality and its impact on customer satisfaction and loyalty. In this study, the dimensions of the mobile service quality frameworks such as SERVQUAL, E-S-QUAL, e-TailQ, M-S-QUAL, and OFD-SERV were used to determine the quality of OFD services in Thailand. To carry out the research, a quantitative approach was chosen. An online survey was used to collect a sample size of 215 respondents from OFD users in Thailand. The data was analyzed using SPSS software, which included descriptive statistics, factor analysis, correlation analysis, and regression analysis. The result shows that only fulfilment of mobile service quality positively impacts customer satisfaction. Simultaneously, satisfaction has a positive impact on both attitudinal and behavioral loyalty. The strong relationship between attitudinal and behavioral loyalty has also been confirmed. Interestingly, customer satisfaction and attitudinal loyalty mediate fulfilment and behavioral loyalty. According to the findings of this study, Thailand users are more concerned with the product than with the system (interface and efficiency) or customer service (contact and responsiveness). Customers in Thailand have low loyalty levels. Despite having a high purchasing frequency, their positive attitude remains low.